The Role of Digital Marketing Technology Assimilation by SMEs - Apasarawirote, Darlin; Yawised, Kritcha (Economics and Business Administration Journal Thaksin University, 2022)
This study investigates factors related to the degree of Digital Marketing Technology (DMT) assimilation by Small and Medium Enterprises (SMEs). This study also proposed a conceptual model to examine at three stages of assimilation: initiation, adoption, and routinization drawing upon theories on contingency settings. The model feature includes five main constructs that was investigated together with its hypotheses. A set of data using 328 participants from SMEs in service sector, were conducted for analysis using multiple regression technique and related statistical tests. The results show that all proposed factors have significantly influenced the DMT assimilation in each stage. The (i) business resilience is significantly and predominantly critical factor in all assimilation stages which follows by (ii) organizational management (at routinization stage), (iii) technological readiness (at adoption stage), (iv) environmental forces (at initiation stage), and (v) business characteristics (at routinization stage). These findings offer insight into how SMEs business owners-managers—would be engage at each assimilation stage of Social Media (SM) and DMT adoption. The novel contribution of this research was to optimize the adoption of DMT so that SME policymakers can create a strategic plan for such an engagement. This empirical study can also help academics better grasp the effects of internal and external factors affecting the assimilation of DMT.